Chemical Weathering of Alumina in Aqueous Suspension at Ambient Pressure: A Mechanistic Study. Issue 12 (10th May 2017) - Abi Aad, Jane; Casale, Sandra; Michau, Mathieu; Courty, Philippe; Diehl, Fabrice; Marceau, Eric; Carrier, Xavier
Abstract: Transition aluminas rank among the main supports used for heterogeneous catalysis. Their stability in the aqueous phase is a key issue for catalytic processes, as their hydration can be strongly detrimental to their physicochemical and mechanical properties. As a consequence, the design of more stable alumina‐based supports relies on a better understanding of the mechanisms leading to their chemical and physical degradation. It is shown here that if suspended in water at atmospheric pressure and at temperatures up to 70 °C, all transition aluminas (from γ to θ‐Al2 O3 ) transform into Al(OH)3 polymorphs (bayerite, gibbsite, and nordstrandite), although to different extents. A quantitative study of the aluminum concentration in solution and of the amount of hydroxides demonstrates that Al2 O3 hydration occurs through a two‐step dissolution/heterogeneous precipitation process, with nucleation of Al(OH)3 on the surface of the alumina grains followed by particle growth. The grains become more fragile because of chemical weathering; the ensuing mechanical degradation by attrition, in turn, brings the weathering process to completion. The nature of the main hydroxide polymorph is a function of aluminum concentration and ageing time: first the kinetic product, bayerite, then nordstrandite and eventually gibbsite, the most thermodynamically stable hydroxide. Increasing crystallinity and decreasing specific surface area of alumina leads to a reduced amount in hydroxide formation. Abstract : Transforming when wet : Transition aluminas are some of the main supports used for heterogeneous catalysis, thus their stability in water is a key issue for catalytic processes. It is shown that all transition aluminas (from γ to θ‐Al2 O3 ) transform into Al(OH)3 polymorphs (bayerite, gibbsite, and nordstrandite), although to different extents, in water up to 70 °C. The nature of the main polymorph is a function of aluminum concentration and ageing time.